Further Implications of Distortion in the Factor Market - Mundlak, Yair (Econometrica, 1970)
in the two sectors. Theorem 2 summarizes the discussion on this subject. The proofs of the proposition leading to Theorems 1 and 2 are illustrated graphically. In order to analyze the effect on the sign of the supply function in this economy, the ES of products with respect to their prices is expressed in terms of the parameters of the individual production functions. The expression shows clearly the augmentation effect observed by Johnson [1] (i.e., in the absence of distortion, the ES between products is larger than those which exist between factors). Finally, Theorem 3 states conditions under which the supply function is increasing, declining, perfectly elastic, or a combination of these.